Weed control efficiency, yield attributes and yield of maize (Zea mays L.) as influenced by weed management practices - A. Mastkar; H. S. Kushwaha; M. L. Kewat (Annals of Agricultural Research, 2022)
A field triat was conducted at Agriculture Farm, Mahatma Gandhi Chitrakoot Gramodaya Vishwavidyalaya, Chitrakoot, Satna (M.P.) during kharif season of 2016 and 2017 to study the weed control efficiency, yield attributes and yield of maize as influenced by various herbicidal treatments under rainfed condition. The experiment comprised of twelve treatments viz. T1 Weedy check (control), T2 Weed free, T3 Mechanical weeding (02), T4 Pendimethalin 1.0 kg a.i./ha PE, T5 Atrazine 1.0 kg a.i./ha PE, T6 Atrazine 0.75 kg a.i./ha + Pendimethalin 0.75 kg a.i./ha PE, T7 Atrazine 1.0 kg a.i./ha fb 2,4-D Amine salt 0.4 kg a.i./ha at 25 days after sowing (DAS), T8 Halosulfuron 0.09 kg/ha at 25 DAS, T9 Atrazine 1.0 kg a.i./ha PE fb Halosulfuron 0.09 kg/ ha at 25 DAS, T10 Tembotrione 0.12 kg a.i./ha at 25 DAS, T11 Pendimethalin 1.0 kg a.i./ha PE fb Atrazine (0.75 kg a.i./ha) + 2,4-D Amine 0.4 kg a.i./ha at 25 DAS and T12 Atrazine 1.0 kg a.i./ha PE fb Tembotrione 0.12 kg a.i./ha at 25 DAS, were carried out in randomized block design with three replications. Data showed that many weed species invaded the experimental field namely Cyperus rotundus, Echinochloa colona, Digera arvensis, Phyllanthus niruri and Convolvulus arvensis. The result showed that pre emergence application of Atrazine 1.0 kg a.i./ha fb Tembotrione 0.12 kg a.i./ha as post emergence applied at 25 DAS had higher weed control efficiency (79.42 %) and mechanical weeded plots (76.19 %) over weedy check. The yield attributes (cob length 19.14 cm., cob weight 148.19 g/plant, grain rows per cob 13.60, grains per row 28.17, number of grains per cob 360.28, grain weight 98.70 g per cob, 100 grain weight 24.05 g), grain (4.67 t/ha) and stover (9.99 t/ha) yields were higher under pre-emergence application of Atrazine 1.0 kg a.i./ha fb Tembotrione 0.12 kg a.i./ ha at 25 DAS